Perceived Barriers to Online Education by Radiologic Science Educators. - Kowalczyk, Nina K. (Radiologic Technology)
Background: Radiologic science programs continue to adopt the use of blended online education in their curricula, with an increase in the use of online courses since 2009. However, perceived barriers to the use of online education formats persist in the radiologic science education community. Purpose: An electronic survey was conducted to explore the current status of online education in the radiologic sciences and to identify barriers to providing online courses. A random sample of 373 educators from radiography, radiation therapy, and nuclear medicine technology educational programs accredited by the Joint Review Committee on Education in Radiologic Technology and Joint Review Committee on Educational Programs in Nuclear Medicine Technology was chosen to participate in this study. Methods: A qualitative analysis of self-identified barriers to online teaching was conducted. Results: Three common themes emerged: information technology (IT) training and support barriers, student-related barriers, and institutional barriers. Discussion: Online education is not prevalent in the radiologic sciences, in part because of the need for the clinical application of radiologic science course content, but online course activity has increased substantially in radiologic science education, and blended or hybrid course designs can effectively provide opportunities for student-centered learning. Conclusion: Further development is needed to increase faculty IT self-efficacy and to educate faculty regarding pedagogical methods appropriate for online course delivery. To create an excellent online learning environment, educators must move beyond technology issues and focus on providing quality educational experiences for students.